2018
DOI: 10.1001/jamanetworkopen.2018.4595
|View full text |Cite
|
Sign up to set email alerts
|

Motivators, Barriers, and Facilitators to Traveling to the Safest Hospitals in the United States for Complex Cancer Surgery

Abstract: Key Points Question What information may motivate the US public to travel to safer hospitals for complex cancer surgery, what barriers to traveling do they face, and what solutions may facilitate appropriately changing hospitals? Findings In this nationally representative survey study, 92% of respondents would be motivated to travel to a specialty cancer hospital for superior safety or oncologic outcomes, but 74% also reported barriers to traveling, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 24 publications
(53 reference statements)
2
73
0
Order By: Relevance
“…[20][21][22][23][24][25] From a patient perspective, travel distance is seen as a barrier to care, and some are willing to accept a higher risk of mortality in order to reduce that burden. 26,27 Average travel distance is particularly long for the rural population. 17,18,20,23,28,29 As cancer care regionalizes, travel may exacerbate disparities for the rural population.…”
mentioning
confidence: 99%
“…[20][21][22][23][24][25] From a patient perspective, travel distance is seen as a barrier to care, and some are willing to accept a higher risk of mortality in order to reduce that burden. 26,27 Average travel distance is particularly long for the rural population. 17,18,20,23,28,29 As cancer care regionalizes, travel may exacerbate disparities for the rural population.…”
mentioning
confidence: 99%
“…Similarly, previous studies have shown that insurance coverage is often a significant barrier to receipt of care at specialized and tertiary care centers. 34 We noted that the change in travel distance was more modest for Medicaid recipients than for patients with commercial insurance or Medicare coverage. Our findings are likely due in part to the geographic features of New York.…”
Section: Results Of the Study In The Context Of Other Observationsmentioning
confidence: 83%
“…Other reassignment models, based on volume or safety performance, predict a larger impact and require as few as 15 patients to change hospitals to save 1 life ( 4 ). Given the many barriers that patients face when choosing hospitals, the likelihood of a reassignment strategy working is almost certainly tied to the number of patients required to move ( 39 ). On the other, the movement of higher risk patients (including those underdoing esophagectomy and pancreaticoduodenectomy) may actually be more reasonable (but again, this is less effective compared with other models).…”
Section: Discussionmentioning
confidence: 99%